A novel protocol to provide a suitable cardiac model from induced pluripotent stem cells. (November 2017) - Rasekhi, Mahsa; Soleimani, Masoud; Bakhshandeh, Behnaz; Sadeghizadeh, Majid
Abstract: Cumulative evidence has proven the safety, feasibility and efficacy of stem cell therapy for cardiomyocyte replacement in heart failure treatment. In contrast to embryonic stem cells, induced pluripotent stem cells (iPS cells) provide a route to the production of patient-specific stem cell lines with no ethical concerns. Recent studies have revealed that myogenic transcription factors activated the expression of conserved microRNAs (miRNAs), such as mir-1, that 'fine-tuned' the output of the transcriptional networks. To introduce an efficient and applicable protocol for establishment of autologous cardiac cellular models, herein we introduced a novel protocol for induction of iPS cells into cardiomyocytes using both microRNA-1 transduction and 5′-Azacitidine treatment. Quantitative evaluation of transcription and translation of cardiac markers such as MHC-α, GATA4, FLK and troponin, demonstrated that this new direct protocol led to cardiac differentiation of iPS cells. From a clinical point of view, these results raise the possibility that administration of miRNA mimic or miRNA inhibitor therapies could increase allocation of iPS cells into the cardiac lineage. Taking all the results into account, our novel protocol provides further progress in the application of patient's own cells for more effective therapies. Moreover, such cellular models could be used in personalized drug screening.